2014
DOI: 10.1002/jez.b.22574
|View full text |Cite
|
Sign up to set email alerts
|

Male claspers in clam shrimps (Crustacea, Branchiopoda) in the light of evolution: A case study on homology versus analogy

Abstract: Male "clam shrimps" possess highly modified first (and second) trunk limbs for clasping the carapace of females during copulation. Claspers are present in all three clam shrimp taxa (Laevicaudata, Spinicaudata, and Cyclestherida) but despite striking similarities in their morphology and function, the matter of their homology is controversial. In this study, we address the question of the homology and evolution of these structures by comparing the developmental transformation of an unspecialized trunk limb into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(47 citation statements)
references
References 27 publications
(36 reference statements)
0
46
1
Order By: Relevance
“…Morphological description follows Kaji et al (2014), Shu et al (2015) and Timms (2016). The following references were consulted for data on Indian leptestheriids: Babu & Nandan (2010), Battish (1981), Daday (1923), Nayar & Nair (1968), Sars (1900), Simhachalam & Timms (2012), Tiwari (1966;1996).…”
Section: Methodsmentioning
confidence: 99%
“…Morphological description follows Kaji et al (2014), Shu et al (2015) and Timms (2016). The following references were consulted for data on Indian leptestheriids: Babu & Nandan (2010), Battish (1981), Daday (1923), Nayar & Nair (1968), Sars (1900), Simhachalam & Timms (2012), Tiwari (1966;1996).…”
Section: Methodsmentioning
confidence: 99%
“…A) Is similar to F in Figure 9. The color coding is from Figure 9 in Kaji et al () and is used to indicated presumed homologous parts (same color = homology; same color coding is used in Figures 12 and 13).…”
Section: Clasper Morphology Functionality and Evolution In Spinicaumentioning
confidence: 99%
“…The large palp is generally homologous in all three taxa, being composed of endite V, with the exception of the presence of a distal outgrowth in the Spinicaudata (Kaji et al, ). The large palp operates in a rather similar way during amplexus in both Spinicaudata and Laevicaudata (Fig.…”
Section: Clasper Morphology Functionality and Evolution In Spinicaumentioning
confidence: 99%
See 1 more Smart Citation
“…10 pairs, first pair modified as claspers. Right and left claspers equal in size and shape, of typical Lynceus form (clasper terminology follows Sigvardt &Kaji et al 2014). Endite 1 of clasper limb typical for genus, lobiform, margined with short setae.…”
Section: Etymologymentioning
confidence: 99%